Patterns of genetic divergence in glacial relict crustaceans - Dooh, Robert T. (University of Guelph, 2003)
Glacial relict taxa have invaded northern freshwater habitats from ancestral populations in Arctic seas. 'Mysis relicta' and 'Limnocalanus macrurus' are two glacial relict crustaceans common to freshwater and saline habitats across the Holarctic. In both taxa, evidence from analysis of the mtDNA gene COI revealed sharp divisions between North American populations in inland waters, versus Arctic coastal. These data indicate that extant inland populations are derived from single freshwater invasion events in each taxon. Despite this similarity, the genetic distance between these phylogeographic groups is several times higher in 'M. relicta' than ' L. macrurus', suggesting that 'M. relicta' gained access to inland North America some millions of years before 'L. macrurus '. This evidence argues for recurrent glacially-mediated invasions versus a common history. A rare but exceptionally divergent lineage of ' L. macrurus' was also identified in Arctic waters, but further allozyme analysis did not conclusively detect phylogeographic structure within this region.